Self‐Regulatory Development in Children from Chinese Immigrant Families: Evidence for Commonality and Specificity. Issue 6 (17th June 2021) - Chen, Stephen H.; Deng, Xue Fang; Zhang, Emily; Wang, Leslie K.; Liu, Cindy H.
Abstract : A central theme of acculturative specificity is the heterogeneity of the immigrant experience. This study integrated this application of the Specificity Principle with intergenerational transmission models of self‐regulation and identified both common and specific pathways in the self‐regulatory development of Chinese American children in immigrant families ( N = 169, M age = 9.2 years). Consistent with intergenerational transmission models, results indicated associations between parents' and children's effortful control, with the mediation of these associations via authoritarian parenting. Parental education, family income, and children's bilingual proficiency were also uniquely associated with children's executive function and effortful control. Together, findings provide new directions for research with ethnic minority immigrant families, and underscore the utility of within‐group approaches in advancing research on ethnic minority children's development.